2019
DOI: 10.1111/jan.14189
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the concept of missed nursing care from a cross‐cultural perspective

Abstract: Aims To investigate how nursing experts and experts from other health professions understand the concept of rationing/missed/unfinished nursing care and how this is compared at a cross‐cultural level. Design The mixed methods descriptive study. Methods The semi‐structured questionnaires were sent to the sample of 45 scholars and practitioners from 26 countries. Data were collected from November 2017–February 2018. Results Assigning average cultural values to participants from each country revealed three cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…The current study found that the Arabic version of the MISSCARE Survey exhibited construct validity and sample adequacy; the KMO for the activities and reasons subscales, respectively, was 0.94 and 0.91, with a significant Bartlett's test of sphericity. These results were consistent with those obtained from the Slovak (0.92) and Czech (0.93) versions, both of which were statistically significant ( p < 0.001) for Bartlett's test of sphericity (Zeleníková et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current study found that the Arabic version of the MISSCARE Survey exhibited construct validity and sample adequacy; the KMO for the activities and reasons subscales, respectively, was 0.94 and 0.91, with a significant Bartlett's test of sphericity. These results were consistent with those obtained from the Slovak (0.92) and Czech (0.93) versions, both of which were statistically significant ( p < 0.001) for Bartlett's test of sphericity (Zeleníková et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…A forward-backward translation was conducted to ensure that the Arabic version measured the same features as the English version. The current study found that the Arabic version of the MISSCARE Survey exhibited construct validity and sample adequacy; the KMO for the activities and reasons subscales, respectively, was 0.94 and 0.91, with a significant Bartlett's test of sphericity.These results were consistent with those obtained from the Slovak (0.92) and Czech (0.93) versions, both of which were statistically significant (p < 0.001) for Bartlett's test of sphericity(Zeleníková et al, 2019).The CFA revealed an adequate fit between the proposed MIS-SCARE Survey model and the observed data. Subscale 2 (reasons for missing care) of the Arabic version of the MISSCARE Survey was crossvalidated using the CFA and other psychometric tests.…”
supporting
confidence: 88%
“…At least three notable limitations apply to this methodological study; first, as the studied concept and its operationalization are highly context‐dependent, comparisons can only be made conditionally (Zeleníková et al., 2019); second, purposive sampling and voluntary participation may have led to selection bias; that is, only persons particularly interested in the studied phenomenon may have participated. In combination with the complex design, this could partly explain the low response rate and the results may not reflect the experience of non‐participants (Vincelette, Thivierge‐Southidara, & Rochefort, 2019); and third, we relied on self‐reporting, which is prone to recall bias and social desirability.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous articles focus on these approaches, but few distinguish clearly between them (Jones et al., 2015; Palese et al., 2019). Yet, attempts for international collaboration are underway to develop standard terminology (Jones, Hamilton, Carryer, Sportsman, & Gemeinhardt, June 2014; Jones, Willis, Amorim‐Lopes, & Drach‐Zahavy, 2019; Zeleníková et al, 2019). Astonishingly, the reviewed literature focuses conceptually mainly on unfinished nursing care and does only implicitly include performed care.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason is the fact that missed nursing care is considered a sensitive issue [21] which may raise feelings of possible self-defense. Therefore, focus groups would give the opportunity to nurses to express their opinions and feelings in more safe and non-blaming environment within the group.…”
Section: Design -Data Collectionmentioning
confidence: 99%